Comparison of desired radiographic advancement distance and true advancement distance required for patellar tendon–tibial plateau angle reduction to the ideal 90° in dogs by use of the modified Maquet technique - Pillard, Paul; Livet, Veronique; Cabon, Quentin; Bismuth, Camille; Sonet, Juliette; Remy, Denise; Fau, Didier; Carozzo, Claude; Viguier, Eric; Cachon, Thibaut (American journal of veterinary research, 2016)
OBJECTIVE To evaluate the validity of 2 radiographic methods for measurement of the tibial tuberosity advancement distance required to achieve a reduction in patellar tendon–tibial plateau angle (PTA) to the ideal 90° in dogs by use of the modified Maquet technique (MMT). SAMPLE 24 stifle joints harvested from 12 canine cadavers. PROCEDURES Radiographs of stifle joints placed at 135° in the true lateral position were used to measure the required tibial tuberosity advancement distance with the conventional (A M ) and correction (A E ) methods. The MMT was used to successively advance the tibial crest to A M and A E . Postoperative PTA was measured on a mediolateral radiograph for each advancement measurement method. If none of the measurements were close to 90°, the advancement distance was modified until the PTA was equal to 90° within 0.1°, and the true advancement distance (TA) was measured. Results were used to determine the optimal commercially available size of cage implant that would be used in a clinical situation. RESULTS Median A M and A E were 10.6 mm and 11.5 mm, respectively. Mean PTAs for the conventional and correction methods were 93.4° and 92.3°, respectively, and differed significantly from 90°. Median TA was 13.5 mm. The A M and A E led to the same cage size recommendations as for TA for only 1 and 4 stifle joints, respectively. CONCLUSIONS AND CLINICAL RELEVANCE Both radiographic methods of measuring the distance required to advance the tibial tuberosity in dogs led to an under-reduction in postoperative PTA when the MMT was used. A new, more accurate radiographic method needs to be developed.